Chitosan coatings with distinct innate immune bioactivities differentially stimulate angiogenesis, osteogenesis and chondrogenesis in poly-caprolactone scaffolds with controlled interconnecting pore size - Caroline D. Hoemann (KeAi Communications Co., Ltd., 2022)
This study tested whether osseous integration into poly (ε-caprolactone) (PCL) bioplastic scaffolds with fully-interconnecting 155 ± 8 μm pores is enhanced by an adhesive, non-inflammatory 99% degree of deacetylation (DDA) chitosan coating (99-PCL), or further incorporation of pro-inflammatory 83% DDA chitosan microparticles (83-99-PCL) to accelerate angiogenesis. New Zealand White rabbit osteochondral knee defects were press-fit with PCL, 99-PCL, 83-99-PCL, or allowed to bleed (drill-only). Between day 1 and 6 weeks of repair, drill-only defects repaired by endochondral ossification, with an 8-fold higher bone volume fraction (BVF) versus initial defects, compared to a 2-fold (99-PCL), 1.1-fold (PCL), or 0.4-fold (83-99-PCL) change in BVF. Hematoma innate immune cells swarmed to 83-99-PCL, elicited angiogenesis throughout the pores and induced slight bone resorption. PCL and 99-PCL pores were variably filled with cartilage or avascular mesenchyme near the bone plate, or angiogenic mesenchyme into which repairing trabecular bone infiltrated up to 1 mm deep. More repair cartilage covered the 99-PCL scaffold (65%) than PCL (18%) or 83-99-PCL (0%) (p < 0.005). We report the novel finding that non-inflammatory chitosan coatings promoted cartilage infiltration into and over a bioplastic scaffold, and were compatible with trabecular bone integration. This study also revealed that in vitro osteogenesis assays have limited ability to predict osseous integration into porous scaffolds, because (1) in vivo, woven bone integrates from the leading edge of regenerating trabecular bone and not from mesenchymal cells adhering to scaffold surfaces, and (2) bioactive coatings that attract inflammatory cells induce bone resorption.